2009
DOI: 10.1136/hrt.2009.166256
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndrome in decompensated heart failure

Abstract: Worsening renal function during treatment of acute decompensated heart failure (ADHF) often complicates the treatment course of heart failure. Furthermore, the development of worsening renal function is a strong independent predictor of long-term adverse outcomes. Sometimes referred to as 'cardiorenal syndrome,' the definition varies widely, and the overall understanding of pathogenesis is limited. This is probably owing to the lack of precision and characterisation of renal compromise during treatment of hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 63 publications
(38 reference statements)
2
71
2
5
Order By: Relevance
“…Increasingly, a spectrum of cardiorenal syndromes, [22][23][24] Gene descriptions include the USA National Centre for Biotechnology Information Reference Sequence accession number. LogFC is the logarithmically transformed fold change in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, a spectrum of cardiorenal syndromes, [22][23][24] Gene descriptions include the USA National Centre for Biotechnology Information Reference Sequence accession number. LogFC is the logarithmically transformed fold change in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, those with worsening renal function often require a longer hospital stay. 17 Worsening renal function is defined in most reports as a change in serum creatinine ≥0.3 mg/ml during hospitalization, and it has been reported to be associated with an increased risk for long-term all-cause/cardiovascular mortality and morbidity in ADHF patients.…”
Section: Aki and Prognosis For Adhf Patientsmentioning
confidence: 99%
“…Recent studies have demonstrated that risk of mortality exponentially increased with increasing stages of AKI in the setting of ADHF (10). Early detection of patients at higher risk for AKI progression would help physicians to plan and initiate the appropriate managements to improve renal safety of therapies, augment surveillance of cardiac and renal dysfunction, and develop renal-preserving treatments (11,12).…”
Section: Introductionmentioning
confidence: 99%